Islamic perspective in Halal Science: analysis of Ijtihad methodology of Halal and Haram in contemporary realities - Busari, Saheed Abdullahi (AIJR Publisher, 2023)
The significance of the Islamic principles of Halal and haram to a sustainable society cannot be overemphasized in the current global struggle against socio-economic, medical, and environ-mental issues. It is fair to say that halal science products and services are becoming attractive to corporate industries, especially in the food, medicine, and entertainment industry. Although re-lated studies in the Halal industry have been gaining attention in recent times with the global economic outlook to hit dollars $4.96 trillion by 2030. However, little is known about the research that speaks to the fundamental Islamic principles of halal and haram in medicine, food, enter-tainment, and service industries. Modern industries are conscious of employing workers that can contribute to the sustainability of the business amid the emerging contemporary realities. This study aims to explicate contemporary Ijtihad methodology of Taḥqīq manāt al-hukm (verifying causal effect existence) and takhrīj manāt al-hukm (coming up with effective cause) in the matter of medicine, pharmaceutical, food, entertainment, and service industry. To this effect, the study employs qualitative methodology in data gathering and analysis of classical and contemporary literature reviews. This study proposes a comprehensive Ijtihad methodology and application to understanding the modern realities of Halal and Haram in food additives using blood plasma.